(3GdMeGjI GdLfGFjI dShb GdChQGb GdeGdjI (B: s (3OQGSI ebGQfI (B/ s - (3gjKe CMeO eMehO SdGegs; (3GHQGgje YjO fGjds; (3CMeO YhV HdGds; (3YeQ SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2011)
(3dbO JfGhd GdHMK ehVhY GdMeGjI GdLfGFjI dShb GdChQGb GdeGdjI h bO CSaQ GdHMK Edi Cf GdhUhd Edi Shb ChQGb eGdjI bhi Ydi OQLI cHjQI ef GdcaGAI JVef MeGjI GdEbJUGO Gdbhei ef GdeeGQSGJ ZjQ GdeTQhYI GdJi jecf Cf jJYQV dgG GdEbJUGO Gdbhei ef GdOGNd Ch GdNGQL (B: (3jSJhLH JhajQ efGN Bef ddGSJKeGQ (B:(3h JKbja eSJeQ ddeJYGedjf OGNd GdShb HCMOK GdbhGfjf (B: (3h QbGHI eMceI h aYGdI ddShb (B: (3h SQYI GdaUd ai GdefGRYGJ GdbVGFjI (B: (3h gh eG jSJhLH EbGeI bVGA eJNUU ai efGRYGJ Shb GdChQGb GdeGdjI h gh CeQ edM dJMbjb GdYOGdI GdWHjYjI ef CLd EbJUGO bhi h eJjf ai HdO JJfGei ajg CfTWJg GdGbJUGOjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2011s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B341-369s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdMeGjI GdLfGFjI s; (3GdeSFhdjI Yf aYd GdZjQ aj LQGFe GdHhQUIs; (3Shb GdChQGb GdeGdjI s; (3GdMeGjI GdLfGFjI dShb GdGehGd GdeGdjI aj GeQjcGs; (3GdMeGjI GdLfGFjI dShb GdGehGd GdeGdjI aj aQfSGs; (3GdMeGjI GdLfGFjI dShb GdGehGd GdeGdjI aj eUQs; (3GdeSFhdjI GdLfGFjI ddGTNGU GdeYfhjIs; (3LQjeI GSJZdGd GdeYdheGJ GdSQjI hGdeejRIs; (3LQGFe GdHhQUIs; (3LQGFe GdJQhjL GdeGdj ZjQ GdbGfhfjs; (3GdLQGFe GdeJYdbI HGdeYdheIs; (3GdLQGFe GdeGSI HTaGajI Shb QGS GdeGds; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs